Exploring the nature and synchronicity of early cluster formation in the Large Magellanic Cloud – IV. Evidence for multiple populations in Hodge 11 and NGC 2210. Issue 4 (30th April 2019) - Gilligan, Christina K; Chaboyer, Brian; Cummings, Jeffrey D; Mackey, Dougal; Cohen, Roger E; Geisler, Douglas; Grocholski, Aaron J; Parisi, M C; Sarajedini, Ata; Ventura, Paolo; Villanova, Sandro; Yang, Soung-Chul; et al.
Abstract: We present a multiple population search in two old Large Magellanic Cloud (LMC) Globular clusters, Hodge 11 and NGC 2210. This work uses data from the Advanced Camera for Surveys and Wide Field Camera 3 on the Hubble Space Telescope from programme GO-14164 in Cycle 23. Both of these clusters exhibit a broadened main sequence with the second population representing (20 ± ∼5) per cent for NGC 2210 and (30 ± ∼5) per cent for Hodge 11. In both clusters, the smaller population is redder than the primary population, suggesting CNO variations. Hodge 11 also displays a bluer second population in the horizontal branch, which is evidence for helium enhancement. However, even though NGC 2210 shows similarities to Hodge 11 in the main sequence, there does not appear to be a second population on NGC 2210's horizontal branch. This is the first photometric evidence that ancient LMC Globular clusters exhibit multiple stellar populations.